Indications for Thrombophilia Screening in Pregnant Patients With Known Inherited Thrombophilias [12L]. (May 2016) - Carroll, Rachel C.; Gupta, Simi; Rebarber, Andrei; Fox, Nathan; Saltzman, Daniel; Lam-Rachlin, Jennifer
Abstract : INTRODUCTION: Inherited thrombophilias are associated with an increased risk of venous thromboembolism during pregnancy. Recommendations for screening for thrombophilias were not available until recently. Inappropriate testing may have led to unnecessary and potentially harmful treatment. The objective of this study was to determine the indications for testing in patients diagnosed with inherited thrombophilias. METHODS: This was a retrospective cohort study of all patients who were diagnosed with a major thrombophilia between 2005–2013 at a single maternal-fetal medicine practice. Major thrombophilias included Factor V Leiden, Prothrombin G20210A, Protein C Deficiency, Protein S Deficiency, and Antithrombin Deficiency. The percentage of patients with appropriate testing and inappropriate testing were calculated. The type of provider who ordered the panel was compared between patients with appropriate and inappropriate screening. RESULTS: 218 patients carried a diagnosis for a major thrombophilia and had a known indication for screening. 36 (16.5%) had an appropriate indication: 19 (8.7%) with a personal history of a VTE and 7.8% with a family history of a VTE or high risk thrombophilia. 182 (83.5%) had an inappropriate indication: 135 (62%) with adverse pregnancy outcomes, 16 (7.3%) with a family history of a low risk thrombophilia, 21 (9.6%) with infertility, and 10 (4.6%) with other indications. There was a significant difference in the types of providers who ordered the panel in patients with appropriate and inappropriate screening. CONCLUSION: The vast majority of patients who were diagnosed with a major thrombophilia would not have been screened according to current guidelines. These diagnoses may lead to unnecessary testing and interventions.